Researcher as an Instrument in Qualitative Research: Challenges and Opportunities - Bahrami, Nasim; Soleimani, Mohammad Ali; Yaghoobzadeh, Ameneh; Ranjbar, Hadi (Advances in Nursing & Midwifery, 2016)
Abstract Background and aim: Researchers, in qualitative researches, both influences on and take effect from the research process. One of the main issues in qualitative research is validity of the researcher as an instrument of data collection. If the researcher does not have enough validity in the data collection, the results of the study will also not be cited. The researcher as instrument provides an opportunity for researchers to enter into the unknown world of individual about the phenomena in question and sometimes faced many challenges in reaching this goal. This study has been reviewing the opportunities and challenges of researchers as an instrument in the qualitative research. Materials and methods: This was a review study on the methodology of qualitative research. Using keywords including qualitative research, instrument, challenges, and opportunities, articles and available books were investigated in PubMed, Scopus, Science Direct, Proquest, Magiran ¡SCI ¡IranDoc, SID, Medlib, IranMedex databases with no time limit. The Quality of the articles was assessed by using the McMaster Critical Review Form for Qualitative studies. Findings: Studies over 12 books and 18 articles showed that the role of the researcher can be varied in different qualitative research designs such as phenomenology researches, grounded theory, ethnography, and content analysis researches. Also previous experience and skills in the process of observation and interview, having effective communication and asking the appropriate questions have an important impact on the role of researchers as a key factor in qualitative research. Conclusions: Researchers have the main role, especially in data gathering of different types of qualitative researches. Actually they are factors that validate the data. Experience and skills, ability to communicate, asking the right questions are the most important factors that have an influence on doing qualitative research in an appropriate ways. Key words: Qualitative Research, Instrument, Challenge, Opportunity REFERENCES ‐ Abedi H A (2010) [Application of phenomenological research in clinical sciences]. Jounal of Rahbord 19(54) 207-24. (persian) ‐ Alvandi S M and Boudlaei H (2010) [Phenomenology in entrepreneurship studies]. Iranian Journal of Management Sciences 5(19) 33-61. (persian) ‐ Bogdan R and Biklen S K (1997). Qualitative research for education, Fourth Edition, New York, Allyn & Bacon, 1997 ] Briggs D (2013) Emotions, ethnography and crack cocaine users. Emotion, Space and Society 7(13) 1-12 ] Brockopp D Y and Hastings-Tolsma M T (2003) Fundamentals of nursing research, Third Edition, Massachusetts, Jones & Bartlett Learning. ] Burns N Grove S K (2010) Understanding nursing research: Building an evidence-based practice, 5th Edition, Philadelphia, Elsevier Health Sciences. ] Corbin J and Strauss A (2014). Basics Of Qualitative Research: Techniques And Procedures For Developing Grounded Theory, Fourth Edition, New York, Sage publications. ] Delavar A (2009) [Qualitative methodology]. Journal of Rahbord. 19(54) 307-29. (persian) ] Dempsey P A and Dempsey A D (2000) Using nursing research: Process, critical evaluation, and utilization. 5th Edition, Philadelphia, Lippincott Williams & Wilkins. ] Emami S A, Dehghan Nayeri N, Rahnavard Z et al. (2012) [Qualitative research methodology: phenomenology]. Holistic Nursing and Midwifery 22(68) 56-63. (persian) ] Feyz D (2010) [The strategic analysis of the role of qualitative research in the country and strategies for its development by SWOT model]. Journal of Rahbord 19(54) 169-85. (persian) ] Gall M D, Borg W R, Gall J P (1996) Educational research: An introduction. 6th Edition, London, Longman Publishing. ] Goetz J P and LeCompte M D (1984) Ethnography and qualitative design in educational research. Second Edition, United States, Academic Press Orlando, FL. ] Hallberg L R (2006) The gcore categoryh of grounded theory: Making constant comparisons. International Journal of Qualitative Studies on Health and Well-being 1(3) 141-48. ] Iman M T Noshadi M R (2011) [Qualitative content analysis] Journal of Pazhuhesh 3(2) 15-44. (pesian) ] Johnson N (2009) The role of self and emotion within qualitative sensitive research: A reflective account. Enquire 2(2) 191-214 ] Khanifar H and Zarvandi N (2010) [Qualitative research: A new approach in management studies]. Journal of Rahbord 19(54) 243-56. (persian) ] Kondracki N L, Wellman N S and Amundson D R (2002) Content analysis: Review of methods and their applications in nutrition education. Journal of Nutrition Education and Behavior 34(4) 224-30 ] Krauss S E (2005) Research paradigms and meaning making: A primer. The Qualitative Report 10(4) 758-70 ] Krippendorff, K. (2012). Content analysis: An introduction to its methodology, New York, Sage Publications ] Lombard M, Snyder-Duch J and Bracken C C (2002) Content analysis in mass communication. Human Communication Research 28(4) 587-604 ] Monadi M (2010) [Qualitative methods and theorization]. Journal of Rahbord 19(54) 107-34 (persian) ] Nourouzi R A and Bidhendi M (2010) [Human agency in qualitative approach to research]. Journal of Rahbord 19(54) 187-206. (persian) ] Pope C, Ziebland S and Mays N (2000) Qualitative research in health care: Analysing qualitative data. BMJ: British Medical Journal 320(7227) 114-6 ‐ Ranjbar H, Haghdoost A A, Salsali M, et al. (2012) [Sampling in qualitative research: A Guide for beginning]. Journal of Army University of Medical Sciences 10(3) 238-250. (Persian) ‐ Rouhani H (2010) [Qualitative research: Background and approaches]. Journal of Rahbord 19(54) 7-29. (persian) ‐ Soleimani M A, Negarandeh, R and Bastani F (2015) [Exploring for self-care Process in patients with parkinson’s disease: A grounded theory study]. Hayat 21(1) 6-22. (persian) ‐ Soleimani M A, Negarandeh R, Bastani F, et al. (2014) Disrupted social connectedness in people with Parkinson’s disease. British Journal of Community Nursing 19(3) 136-4. ‐ Speziale H S, Streubert H J and Carpenter D R (2011) Qualitative research in nursing: Advancing the humanistic imperative, Philadelphia, Lippincott Williams & Wilkins. ‐ Steen M and Roberts T (2011) The handbook of midwifery research. 1st Edition, New Jersey, John Wiley & Sons. ‐ Weeks M R and Schensul J J (2014) Ethnographic Research on AIDS Risk Behavior and the Making of Policy. Speaking the Language of Power: Communication, Collaboration and Advocacy (translating Ethnology Into Action) 50. ‐ Yin R K (2013) Case study research: Design and methods, 5th Edition, New York, Sage publications.